Recommendations on diagnosis and treatment of depression in patients with multiple sclerosis. Issue 4 (5th February 2014) - Fragoso, Yara Dadalti; Adoni, Tarso; Anacleto, Andrea; da Gama, Paulo Diniz; Goncalves, Marcus Vinicus Magno; Matta, Andre Palma da Cunha; Parolin, Monica Fiuza Koncke
Abstract : Multiple sclerosis (MS) is frequently associated with depression. Yet there are few clinical trials on treating depression in MS and no agreed recommendations for its assessment and follow-up. We present evidence-based recommendations for several aspects of depression in MS, including screening for depression, recognition of other concomitant psychiatric conditions, suicide risk, disability, fatigue, cognition, adherence to treatment, the effect of drugs used to treat MS on depression and possible pharmacological treatments for depression in MS.